DETERMINING OPTIMAL SIZE, POSITION AND COVERING MATERIAL FOR A BUSHING SHIELD - Glotiđ, Adnan; Kitak, Peter; Pihler Jože; Tičar, Igor (Journal of Energy Technology, 2024)
This paper deals with the design optimization of insulating elements-bushings. The principle of the shield size and its position as well as the insulating material determination, based on an optimization processis presentedon the example of a bushing. The aimoftheoptimizationwas to a chieve lowest electrical fields treng thvaluesaroundabushingand the lowe stratio of the electrical fields trengthvaluesat the border of twodifferentdi electric materials; the bushings body and the dielectri clayer that covers a shield. High electrical field streng thvaluesareone amongfactors, which can dramaticallyde crease the in sulators’ operational reliability; there fore the optimal design of a bushing with lowest electrical field strength values is desirable. An optimization procedure was carried out using Differential Evolution (DE) Algorithm combined with the solver of the software tool EleFAnT for solving a parametrically -written model of a bushing. EleFAnTisbasedon finite element method (FEM) with a preͲ processo rthat was made in the MATLAB soft ware tool.